Research during medical school: is it particularly difficult in developing countries compared to developed countries? - Siddaiah-Subramanya, Manjunath (Adv Med Educ Pract, 2017)
OBJECTIVES: Medical student involvement in research has been declining over the years. We reviewed the factors that hinder participation in research with a focus on developing countries. METHODS: Literature search was performed using PubMed, MEDLINE and Cochrane Library. Peer-reviewed articles published between 1995 and 2017 were screened for relevance to identify key factors affecting medical student involvement in research with a particular focus on developing world. Analytical review is presented here in this article in relation to commonly reported aspects related to research during medical school. RESULTS: This search revealed varied contributing factors that hinder students’ growth and interest in research. It commonly highlighted few aspects in relation to research during medical school, and they were “variability in research uptake among students and issues related to them, their knowledge and attitude toward research and organizational input and its influence on students”. CONCLUSION: While early introduction to research by inculcating a mindset aimed at research has been proposed, it has not been seen in practice during either the medical school or beyond to an extent that was expected. It appears that developing countries, while they share some of the reasons with developed countries, have their own set of difficulties, which are influenced by culture, beliefs and priorities.